Performance of Ground Clay Brick Mortars in Simulated Chloride and Sulphate Media - Festus Ngui Musyimi; Jackson Muthengia Wachira; Joseph Karanja Thiong’o; Joseph Mwiti Marangu (Journal of Engineering)
The durability of cement-based structures majorly depends on their resistivity to the aggressive media in the construction environment. The most aggressive ions commonly encountered in construction environment are chloride (Cl−) and sulphate (SO42−). The interactions of these ions with hydrated cement influence their durability and ultimate service life. This paper reports the experimental findings on an investigation on the diffusivity of Cl− and SO42− ions into mortars made from two mixtures: one made from ground calcined clay bricks (GB) and commercial ordinary Portland cement (OPC) and the other consisting of GB and Portland pozzolana cement (PPC). The test media were 3.5% Cl− and 1.75% SO42− solutions. For comparison, commercial OPC and PPC were also investigated. GB was blended with OPC at replacement levels of 25, 35, 45, and 50% to make OPCGB. Similar blends were also made with PPC replacement levels of 15, 20, and 25% to make PPCGB. Mortar prisms measuring 160 mm × 40 mm × 40 mm were cast at the water-to-cement ratios (w/c) of 0.40, 0.50, and 0.60 using each category of cement and cured in water for 3, 7, and 28 days. Compressive strength measurements were taken at each of the curing ages. The 28-day cured mortar prisms were subjected to compressive strength analysis and accelerated Cl− and SO42− ingress for 36 hours at 12 V. Ion profiling was done on the mortars, and diffusion coefficients of the Cl− and SO42− ions were approximated. The results showed that there was an increase in compressive strength after exposure to Cl− and SO42− ions. In addition, the ingress of Cl− and SO42− ions decreased with an increase in depth of cover. Blended cement exhibited lower Cl− and SO42− ingress than OPC. The ingress of Cl− was observed to be higher than that of SO42− ions. The ingress of Cl− and SO42− ions increased with an increase in w/c ratio. The results further showed that there was a drop in the ingress of Cl− and SO42− ions with an increase in replacement up to 35 percent for OPC. A 15 percent replacement showed a better compressive strength development compared with 20 and 25 percent replacement for PPC. Blended cement showed lower apparent diffusion coefficients (Dapp) compared with OPC. PPC, OPCGB-35, and PPCGB-15 exhibited similar performance in terms of strength development, aggressive ions ingress, and Dapp. In conclusion, it was found that the test cements, PPCGB-15 and OPCGB-35, can be used in similar tested environments as commercial PPC.